2004
DOI: 10.1136/adc.2003.028159
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal transport: problems in neonatal intensive care capacity

Abstract: Objective: To assess the quantity and nature of transfers within the Yorkshire perinatal service, with the aim of identifying suitable outcome measures for the assessment of future service improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 4 publications
0
12
2
Order By: Relevance
“…Although the referrers potentially did not cite all reasons for transfer (it is not necessary for the referrer to justify the transfer to the call handler so they may choose to cite one reason only), capacity of neonatal units continues to be a significant factor for IUT referrals. Fourteen years ago, in almost the same geographical region, Gill and colleagues demonstrated that in 73% of their cohort, the reason for IUT was the predicted need for an appropriate neonatal cot . Our data show 63% of transfers occur because of capacity reasons (58% specifically due to neonatal cot capacity) and 33.9% for gestation reasons, demonstrating capacity remains a problem for many units.…”
Section: Discussionmentioning
confidence: 60%
“…Although the referrers potentially did not cite all reasons for transfer (it is not necessary for the referrer to justify the transfer to the call handler so they may choose to cite one reason only), capacity of neonatal units continues to be a significant factor for IUT referrals. Fourteen years ago, in almost the same geographical region, Gill and colleagues demonstrated that in 73% of their cohort, the reason for IUT was the predicted need for an appropriate neonatal cot . Our data show 63% of transfers occur because of capacity reasons (58% specifically due to neonatal cot capacity) and 33.9% for gestation reasons, demonstrating capacity remains a problem for many units.…”
Section: Discussionmentioning
confidence: 60%
“…In our country, there is still no official regulation providing the standardization of the epicrisis paper which includes birth report, identitiy and gender information and written referral information. Unstandardized referrals are known to lead not only to medical problems, but also social and legal problems (including mixing of patients and wrong designation of gender) (26). In our study, the rates of absence of pre-transport communication (compromising service work force and coordination), abscence of written epicrisis (causing to lack of medical data and delay in approach to the patient) and abscence of birth report and identity and gender information (leading to legal complications) were found to be decreased in the second group.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a reluctance to drive this standard from the centre, leaving individual networks to work out how to work towards it. There is now evidence that the combined ''intensive care'' capacity of district hospitals may be greater than that of the tertiary centres, 22 but financially and logistically it is simply not possible to support the development of full intensive care services at these sites. Without appropriate investment in the near future, neither will there be the capacity within network tertiary centres in most areas to accept the work currently done at these designated ''level 2'' units and thus it will be impossible to meet this NSF standard in many areas.…”
Section: How Were Network Established?mentioning
confidence: 99%